Saccharomyces boulardii CNCM I‐745 supplementation modifies the fecal resistome during Helicobacter pylori eradication therapy. Issue 2 (6th January 2022) - Cifuentes, Sara Gabriela; Prado, María Belén; Fornasini, Marco; Cohen, Henry; Baldeón, Manuel Eduardo; Cárdenas, Paúl Andrés
Abstract: Background: The gut microbiota is a significant reservoir of antimicrobial resistance genes (ARGs). The use and misuse of antimicrobials can select multi‐resistant bacteria and modify the repertoire of ARGs in the gut. Developing effective interventions to manipulate the intestinal resistome would allow us to modify the antimicrobial resistance risk. Materials and Methods: Applying shotgun metagenomics, we compared the composition of fecal resistome from individuals treated with triple therapy for Helicobacter pylori plus Saccharomyces boulardii CNCM‐I 745 ( Sb ) versus triple antibiotherapy without S . boulardii (control) before, after, and one month after treatments. DNA samples were sequenced on an Illumina NovaSeq 6000 platform. Reads were trimmed and filtered for quality, and the reads classified as host genome were removed from further analysis. We used the ResFinder database for resistome analysis and the web‐based tool ResistoXplorer and RStudio for graphical representation and statistical analysis. Results: We identified 641 unique ARGs in all fecal samples, conferring resistance to 18 classes of antibiotics. The most prevalent ARGs found in at least 90% of the samples before the treatments were against tetracyclines, MLS‐B (macrolide, lincosamide, and streptogramin B), beta‐lactams, and aminoglycosides. Differential abundance analysis allowed the identification of ARGs significantly different between treatment groups. Thus, immediately after the treatments, the abundance of ARGs that confer resistance to lincosamides, tetracyclines, MLS‐B, and two genes in the beta‐lactam class ( cfxA 2 and cfxA 3) was significantly lower in the group that received Sb than in the control group (edgeR, FDR <0.05). Conclusion: Our study demonstrated that the addition of S . boulardii CNCM‐I 745 to the conventional antibiotic eradication therapy for H . pylori reduced the abundance of ARGs, particularly those genes that confer resistance to lincosamides, tetracyclines, MLS‐B, and a few genes in the beta‐lactams class.